Legal Study of the Advising Bank's Recourse Rights and the Application of Letters of Indemnity in Letter of Credit Deals - Aufa, Muhammad Fikri (Jurnal Ilmiah Kutei, 2026)
In international commercial transactions, the Issuing Bank issues Letters of Credit through banking services. The bank is required to make payments to exporters. Documentary credit is a common and secure payment technique used by parties interested in international trade. However, the Issuing Bank failed to pay the L/C, thus the advising bank exercised its recourse rights by issuing a letter of indemnity. The difficulty in this article is to determine when the advising bank's recourse rights are exercised and the method for sending a letter of indemnity. The normative legal research method was applied in this study. According to the discussion, recourse rights can be used by including them in the L/C contract or trade contract and sending a letter of indemnity to the exporter as a form of payment guarantee, and recourse rights are made with a notification letter to the issuing bank stating the grace period for orderly payment.